2020
DOI: 10.1123/jpah.2019-0230
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With 24-Hour Movement Guidelines in Hong Kong Adolescents: Associations With Weight Status

Abstract: Background: This study examined the compliance with the 24-Hour Movement Guidelines among Hong Kong adolescents and its associations with body mass index (BMI). Methods: A total of 1039 adolescents (11–18 y) wore the activPAL™ for 24 hours for 7 consecutive days to assess physical activity (PA) and sleep duration. Screen time was measured using the Children’s Leisure Activities Study Survey (Chinese version). Linear mixed models were performed for analysis. Results: The analytic sample consisted of 692 adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 25 publications
13
58
1
1
Order By: Relevance
“…We found that around half of the Asian adolescents did not meet any of the three guidelines, and less than 1% of the adolescents met all the three guidelines with an exception of those from Shanghai (3%). Similar results have been revealed in adolescents from other countries and subnational regions such as Canada (10), Hong Kong (11) and Korea (12).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found that around half of the Asian adolescents did not meet any of the three guidelines, and less than 1% of the adolescents met all the three guidelines with an exception of those from Shanghai (3%). Similar results have been revealed in adolescents from other countries and subnational regions such as Canada (10), Hong Kong (11) and Korea (12).…”
Section: Discussionsupporting
confidence: 88%
“…From such a movement continuum perspective, children and adolescents aged 5 to 17 years are recommended to engage in at least 60 minutes of moderate-to-vigorous PA (MVPA), spend no more than 2 hours in recreational screen-time, and sleep 9-11 hours for those aged 5-13 years and 8-10 hours for those aged 14-17 years in daily life (9). Still, data on the movement behaviours are common for preschool-and school-aged children (Carson, Tremblay, & Chastin, 2017;Chaput et al, 2017;Walsh et al, 2018), and only few research has shown this knowledge in adolescents (10)(11)(12). A recent study found that 17.1% Canadian adolescents aged 12-17 years did not meet any of the PA, recreational screen-time, sleep duration guidelines and only 5.5% of those met all the three guidelines (10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given issues concerning pediatric obesity in China [6,7], research examining adherence to the 24-h movement guidelines may be timely. However, few studies have examined adherence to 24-h movement guidelines in China [7,13,20]. For example, Guan and colleagues [7] examined the proportion of children (aged 4.1 to 6.3 years) from three kindergartens in Beijing meeting movement guidelines suggested by the World Health Organization, and reported that just 15.0% met all three guidelines, and 2.7% did not meet any guidelines.…”
Section: Introductionmentioning
confidence: 99%